Postcranial axial skeleton of Europasaurus holgeri, (Dinosauria, Sauropoda) from the Upper Jurassic of Germany: implications for sauropod ontogeny and phylogenetic relationships of basal Macronaria - Carballido, José Luis (2013)
Neosauropods are well represented in the Late Jurassic fossil record, both in Laurasia and Gondwana. Among Macronaria,Europasaurus represents one of the most basal forms of this group. In addition to its systematic importance, Europasaurus is also the first unequivocal dwarf sauropod from which adult and juvenile material is available. Despite the abundance of sauropods in the fossil record, early juvenile specimens are rare, limiting knowledge about sauropod ontogeny. Therefore, the great amount of material of Europasaurus provides an excellent opportunity to improve our knowledge on the early evolution of Macronaria, as well as to shed light on some morphological changes through ontogeny. The postcranial axial skeleton of sauropods is extremely modified with respect to the anatomy observed in its ancestors, the ?prosauropods?, proving to be one of the most informative regions of the body. Here we provide a detailed description of the axial skeleton of Europasaurus, including adult and juvenile elements, discussing its systematic and ontogenetic importance. We also analyse the phylogenetic position of Europasaurus through a cladistic analysis using TNT, which retrieves this taxon in a basal position among Camarasauromorpha. Additionally, the presence/absence of discrete characters and the comparison of juvenile elements with adult specimens allowed us to recognize different morphological ontogenetic stages (MOS). Whereas early stages lack derived characters (e.g. spinodiapophyseal lamina and prespinal lamina on dorsal vertebrae), all derived characters (including autapomorphies) are present in late immature specimens. Therefore, while late immature specimens provide the same phylogenetic signal as adult specimens of Europasaurus, more immature stages are recovered in a basal position among sauropods. Finally, we apply the MOS to other maturity criteria (e.g. neurocentral closure, sexual maturity) in a search for a wider definition of maturity.